Nanometer heat insulation transparent coating material special for glass and preparation method of nanometer heat insulation transparent coating material

Through the ternary combination technology of nano ATO, LaB6 and TiN powder, the problem of insufficient infrared light regulation of 780 nanometers to 1500 nanometers in the existing technology is solved, and a nano transparent thermal insulation coating material with high transmittance and infrared barrier is realized , suitable for industrial production and meet the needs of different fields.

CN119220159APending Publication Date: 2024-12-31BEIJING ZHONGKE JIEDA NANOMETER SUPPLY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310792585.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing glass-specific nano-transparent thermal insulation coating materials have shortcomings in the regulation of infrared light from 780 nanometers to 1500 nanometers, and ITO powder resources will be exhausted by the middle of this century, making it difficult to meet market demand.

Method used

Using the ternary combination technology of nano ATO powder, nano LaB6 powder and nano TiN powder, an aqueous polyurethane with high permeability and infrared barrier effect can be prepared by combining alcohol dispersion liquid, silane coupling agent and surfactant. Alcohol-soluble resin coating materials use the advantages of ternary composite nanomaterials to improve the thermal insulation effect.

Benefits of technology

It realizes effective barrier to thermal infrared light, ensures a visible light transmittance of ≥70%, and significantly improves the thermal insulation effect, is suitable for large-scale industrial production, and can adjust the hardness of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention relates to a nano heat-insulation transparent coating material which takes nano ATO, LaB6 and TiN powder as fillers, is prepared from ternary combination waterborne polyurethane or alcohol-soluble resin and is special for glass, and a preparation method of the nano heat-insulation transparent coating material. The nano heat-insulation and heat-preservation transparent coating material is characterized in that waterborne polyurethane or alcohol-soluble resin is used as a film forming substance, nano ATO, LaB6 and TiN powder are used as fillers, and the transparent coating material which can be used for an infrared barrier film special for glass is prepared by using materials such as a silane coupling agent, a surfactant and a multifunctional additive through methods such as high-speed shearing, ball milling and dispersing. The thickness of the coating is preferably 30-70 nanometers, and the hardness of the coating can be adjusted between 1H and 5H. On the premise that the visible light transmittance is larger than or equal to 70%, the infrared shielding rate can reach 50% or above, the indoor and outdoor temperature and the temperature inside and outside a carriage are balanced, the service time of an air conditioner or an electric heater device is shortened as much as possible under the environment that the human body comfort and good work are guaranteed, and the optimal effects of energy conservation and emission reduction are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the technical field of nano heat-insulating transparent coating materials for glass, and in particular relates to a novel nano transparent heat-insulating coating material comprising nano ATO powder, nano LaB6 powder and nano TiN powder, a ternary combination of filler and silane coupling agent, surfactant, multifunctional auxiliary agent and deionized water, and water-based polyurethane or alcohol-soluble resin. [Background technology]

[0004] In use, on the one hand, the glass is required to have good visible light transmittance, reaching ≥70% lighting performance, and at the same time must ensure that the infrared in the heat energy can be limited. In some special industries and special fields, it is also required to have some special heat insulation and thermal insulation properties. This has brought huge business opportunities for the development of nano-transparent heat insulation coating materials and nano-heat insulation glass dedicated to glass.

[0005] At present, relevant research institutions have conducted research on thermal infrared shielding control. However, among these research institutions, most of them use antimony tin oxide (ATO) and indium tin oxide (ITO) as the main fillers. For ATO, its main shielding band is generally greater than 1500 nanometers, while ITO can control infrared rays with wavelengths between 780 nanometers and 1500 nanometers to a certain extent. However, with the depletion of resources, it is expected that by the middle of this century, the indium element that can be collected on the earth will be exhausted, which greatly limits the use of ITO powder. However, if only ATO powder is used in glass, it is difficult to regulate near-infrared light from 780 nanometers to 1500 nanometers (this part of light accounts for about 20-30% of the energy in sunlight). Therefore, it is necessary to develop a new type of nano-transparent thermal insulation coating material with a ternary combination as a filler to meet the current market needs. [Summary of the invention]

[0006] [Technical issues to be solved]

[0007] The purpose of the present invention is to solve the existing technical defects and provide a new type of nano transparent heat insulating glass coating material with a ternary combination as filler;

[0008] Another object of the present invention is to provide a method for preparing the novel ternary combination nano transparent thermal insulation glass coating material.

[0009]

Technical solution

[0010] The present invention is achieved through the following technical solutions:

[0011] The invention is characterized in that it utilizes ternary combination nano-shielding thermal infrared technology and ternary composite nano-materials to carry out suitable selective compounding and modification treatment on the micron-level materials in the components, so as to prepare a novel nano-thermal insulation transparent coating material which can ensure a visible light transmittance of ≥70% and has a certain infrared shielding heat insulation effect, and the coating film has a certain hardness which can be adjusted between 1 and 5 hours.

[0012] In order to solve the technical problem of more effective thermal infrared shielding, the present invention adopts the ternary combination thermal insulation principle of nano ATO powder, nano LaB6 powder and nano TiN powder, and the comprehensive technical scheme of complementary advantages of the three effectively improves the blocking and shielding rate of thermal infrared light by the coating material for nano transparent thermal insulation glass described in the present invention, and significantly improves the thermal insulation effect of the nano transparent thermal insulation glass coating.

[0013] The present invention takes the following main steps:

[0014] Step 1: Prepare the alcohol dispersion of nanopowder at room temperature

[0015] 1. ATO powder dispersion: weigh the powder and mother liquor in a weight ratio of 40%, add 5% polyethylene glycol surfactant and 2% silane coupling agent, put into a homogenizing emulsifier and disperse under high-speed ball milling for 1-24h;

[0016] Preparation of ATO powder dispersion: ATO powder mother liquor 40% + polyethylene glycol 5% + silane coupling agent 2% = ball milling. Disperse for 1-24h;

[0017] 2. LaB6 dispersion: weigh powder and mother liquor at a ratio of 40%, add 5% polyvinyl pyrrolidone surfactant, put into homogenizing emulsifier and disperse under high-speed ball mill for 1-24h;

[0018] Preparation of LaB6 dispersion: 40% LaB6 powder mother solution + 5% polyvinyl pyrrolidone = ball mill. Disperse for 1-24h;

[0019] 3. TiN dispersion: weigh powder and mother liquor at a weight ratio of 40%, add 5% polyvinyl pyrrolidone surfactant, put into a homogenizing emulsifier, and disperse under high-speed ball milling for 1-24 hours;

[0020] Preparation of TiN dispersion: TiN powder mother solution 40% + polyvinyl pyrrolidone 5% = ball mill. Disperse for 1-24 hours.

[0021] Step 2: Preparation of coating materials for ternary composite nano-transparent heat-insulating glass

[0022] Weigh 70% of the film-forming substance by weight, put 30% of the alcohol dispersion by weight into a homogenizing emulsifier, add it to the film-forming substance under high-speed shear stirring, and add an appropriate amount of auxiliary agent at the same time.

[0023] As a further improvement of the preparation method of the ternary combination nano transparent thermal insulation coating material:

[0024] Preferably, the mother liquid of the alcohol-soluble dispersion is selected from: ethanol, ethylene glycol, methanol or one or a mixture thereof.

[0025] Preferably, the alcohol-soluble dispersion is prepared by high-energy ball milling for 1-24 hours.

[0026] Preferably, the film-forming material is selected from water-based polyurethane series, alcohol-soluble resin series, etc.

[0027] The beneficial effects relative to the prior art are:

[0028] 1. The transmittance spectrum of the target product was measured. The results show that the coating has achieved a ternary combination and synergistic effect. It combines the advantages of ATO, LaB6 and TiN nanopowders and has a strong infrared blocking effect. The infrared blocking rate can reach ≥50% while ensuring that the visible light transmittance is ≥70%.

[0029] 2. The preparation method is simple, scientific, effective, energy-saving and low-cost, and is suitable for large-scale industrial production.

[0030] 3. The hardness of the transparent functional coating is controllable, which can well meet the needs of different conditions in different fields. [Specific implementation method]

[0031] The present invention will be better understood through the following examples.

[0032] First, buy from the market

[0033] ATO powder, LaB6 powder and TiN powder as infrared blocking agents

[0034] Water-based polyurethane, alcohol-soluble resin, etc. as film-forming materials

[0035] Anhydrous ethanol, methanol, ethylene glycol, etc. as dispersion mother liquid

[0036] then

[0037] [Example]

[0038] Example 1: Preparation Example of Ternary Combination Nano Transparent Thermal Insulation Glass Coating Material:

[0039] A. Prepare the alcohol dispersion of nanopowder at room temperature

[0040] 1. First, weigh the ATO powder dispersion according to the weight ratio of 40% powder and mother liquor, then add 5% polyethylene glycol surfactant and 2% silane coupling agent, put into the homogenizing emulsifier disperser and disperse under high-speed ball mill for 24 hours;

[0041] 2. Then weigh the powder and mother liquor of LaB6 dispersion according to 40% by weight, add 5% polyvinyl pyrrolidone surfactant, put into homogenizing emulsifier and disperse under high-speed ball mill for 24 hours;

[0042] 3. Finally, weigh the powder and mother liquor according to the weight ratio of 40% of the TiN dispersion, add 5% of polyvinyl pyrrolidone surfactant, put it into a homogenizing emulsifier and disperse it under high-speed ball milling for 24 hours;

[0043] B. Preparation of coating materials for ternary composite nano-transparent heat-insulating glass

[0044] Weigh 70% of the film-forming material by weight, put 15% of the ATO dispersion, 10% of the LaB6 dispersion and 5% of the TiN dispersion into a homogenizing emulsifying disperser, add them to the film-forming material under shearing and dispersing stirring at 1000rpm, and add 0.5% of KH570, 1% of polyethylene glycol and 2% of ethylene glycol by weight. After mixing and stirring evenly, a transparent heat-insulating coating material for ternary composite nano glass is obtained.

[0045] Example 2: Preparation of a ternary composite nano-transparent heat-insulating glass coating material

[0046] The implementation steps of this embodiment are as follows:

[0047] A: Prepare an alcohol dispersion of nanopowder at room temperature.

[0048] 1. First, weigh the ATO powder dispersion according to the weight ratio of 30% powder and mother liquor, then add 3.5% polyethylene glycol surfactant and 1.5% silane coupling agent, put into the homogenizing emulsifier, and disperse for 20 hours under high-speed ball milling;

[0049] 2. Then weigh the powder and mother liquor of LaB6 dispersion according to 20% by weight, add 4% polyvinyl pyrrolidone surfactant, put into homogenizing emulsifier, and disperse for 20 hours under high-speed ball milling;

[0050] 3. Finally, weigh the powder and mother liquor of TiN dispersion according to the weight ratio of 10%, add 5% polyvinyl pyrrolidone surfactant, put into the homogenizing emulsifier, and disperse for 20 hours under high-speed ball milling;

[0051] B: Preparation of ternary nano-transparent thermal insulation glass coating material

[0052] Weigh 75% of the film-forming material by weight, add 10% of the ATO dispersion, 15% of the LaB6 dispersion and 5% of the TiN dispersion into a homogenizing emulsifying disperser, add them to the film-forming material under shearing, dispersing and stirring at 1000rpm, and add 1% of KH570, 1.5% of polyethylene glycol and 1.5% of ethylene glycol at the same time. After mixing, dispersing and stirring evenly, a ternary composite nano transparent heat insulating glass coating material is obtained.

[0053] Example 3: Preparation of a ternary composite nano-transparent heat-insulating glass coating material

[0054] The implementation steps of this embodiment are as follows:

[0055] A: Prepare the alcohol dispersion of nanopowder at room temperature

[0056] 1. First, weigh the ATO powder dispersion according to the weight ratio of 20% powder and mother liquor, then add 2% polyethylene glycol surfactant and 1% silane coupling agent, put into the homogenizing emulsifier disperser, and disperse under high-speed ball milling for 15 hours;

[0057] 2. Then weigh the powder and mother liquid according to the weight ratio of 15% of LaB6 dispersion, add 3% polyvinyl pyrrolidone surfactant, and disperse it under high-speed ball milling for 15 hours;

[0058] 3. Finally, weigh the powder and mother liquor of TiN dispersion according to the weight ratio of 10%, add 5% polyvinyl pyrrolidone surfactant, put into the homogenizing emulsifier, and disperse for 20 hours under high-speed ball milling;

[0059] B: Preparation of ternary nano-transparent thermal insulation glass coating material

[0060] Weigh 77.5% of the film-forming material by weight, put 2% of the ATO dispersion, 18% of the LaB6 dispersion and 5% of the TiN dispersion into a homogenizing emulsifying disperser, add them to the film-forming material under shearing, dispersing and stirring at 1000rpm, and add 0.5% of KH570, 1% of polyethylene glycol and 1% of ethylene glycol at the same time. After mixing, dispersing and stirring evenly, a ternary composite nano transparent heat-insulating glass coating material is obtained.

[0061] Example 4: Preparation of a ternary composite nano-transparent heat-insulating glass coating material

[0062] The implementation steps of this embodiment are as follows:

[0063] A: Prepare the alcohol dispersion of nanopowder at room temperature

[0064] 1: Prepare the alcohol dispersion of nanopowder at room temperature. The TiN powder dispersion is weighed in a 15% ratio of powder and mother liquid, and then add 1.5% of polyethylene glycol surfactant and 0.5% of silane coupling agent, and disperse under high-speed ball milling for 10 hours;

[0065] LaB6 dispersion was prepared by weighing powder and mother liquor at a ratio of 10%, adding 2% polyvinyl pyrrolidone surfactant, and dispersing under high-speed ball milling for 10 h;

[0066] B: Preparation of ternary nano-transparent thermal insulation glass coating material

[0067] Weigh 77.5% of the film-forming material in proportion, add 2% of the TiN dispersion and 18% of the LaB6 dispersion into the film-forming material under shear stirring at 1000rpm, and add 0.5% of KH570, 1% of polyethylene glycol, and 1% of ethylene glycol at the same time. After mixing and stirring evenly, a transparent heat-insulating coating for glass is obtained.

[0068] Example 5: Preparation of a ternary composite nano-transparent heat-insulating glass coating material

[0069] The implementation steps of this embodiment are as follows:

[0070] A: Prepare the alcohol dispersion of nanopowder at room temperature

[0071] Step 1: Prepare an alcohol dispersion of nanopowder at room temperature. The ATO powder dispersion is prepared by weighing the powder and the mother liquor at a ratio of 10%, adding 1.5% of polyethylene glycol surfactant and 0.5% of silane coupling agent, and dispersing under high-speed ball milling for 5 hours;

[0072] TiN dispersion was prepared by weighing powder and mother liquid at a ratio of 5%, adding 2% polyvinyl pyrrolidone surfactant, and dispersing under high-speed ball milling for 5 h;

[0073] B: Preparation of ternary nano-transparent thermal insulation glass coating material

[0074] Weigh 77.5% of the film-forming material in proportion, add 18% of the ATO dispersion and 2% of the TiN dispersion into the film-forming material under shear stirring at 1000 rpm, and add 0.5% of KH570, 1% of polyethylene glycol, and 1% of ethylene glycol at the same time. After mixing and stirring evenly, a transparent heat-insulating coating for glass is obtained.

[0075] Obviously, those skilled in the art can make various changes and modifications to the transparent heat-insulating coating of the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A nano transparent coating material specially used for heat-insulating glass, characterized in that It is composed of the following components, in parts by weight: The nano transparent coating material specially used for heat insulating glass is characterized by: The heat-insulating glass transparent coating material is a multi-component composite nano transparent coating material that makes each component work synergistically. The coating material is a heat-insulating glass transparent coating material that uses 15-20% nano antimony tin oxide (ATO), 20-25% lanthanum hexaboride (LaB6) and 10-15% nano titanium nitride (TiN) powder as fillers and 25-35% water-based polyurethane and alcohol-soluble resin, and is compounded by adding 8-10% silane coupling agent, 3-5% surfactant and 3-5% multifunctional additives (thickener, leveling agent, wetting agent, antibacterial agent, curing agent) and other functional additives, and is prepared by high-speed shear dispersion or ball milling dispersion and other process technology means.

2. The preparation method of the nano transparent coating material for heat insulating glass according to claim 1 is as follows: Step 1: Prepare an alcohol dispersion of nanopowder at room temperature; Step 2: Add the alcohol-soluble dispersion into a certain amount of film-forming material in a certain proportion under stirring.

3. The alcohol-soluble dispersion of the nanopowder according to claim 2, wherein the dispersion matrix used is ethanol, ethylene glycol, methanol, etc.

4. The alcohol-soluble dispersion of the nanopowder according to claim 2, characterized in that The ATO dispersion is prepared by weighing 10 grams of ATO nano powder, 15 grams of alcoholic matrix material, adding 0.1-2 grams of surfactant and 0.1-2 grams of coupling agent, and then putting the mixture into a ball milling jar for 0.5-24 hours and then taking it out.

5. The alcohol-soluble dispersion of the nanopowder according to claim 2, characterized in that The nano-dispersion liquid is prepared by weighing 10 grams of LaB6 nano-powder, 15 grams of alcoholic matrix material, adding 0.1-2 grams of surfactant and 0.1-2 grams of coupling agent, and then putting the nano-dispersion liquid into a ball milling jar for 0.5-24 hours and then taking it out.

6. The alcohol-soluble dispersion of the nanopowder according to claim 2, characterized in that The TiN dispersion is prepared by weighing 10 grams of TiN nanopowder, 15 grams of alcoholic matrix material, adding 0.1-2 grams of surfactant and 0.1-2 grams of coupling agent, and then putting the mixture into a ball milling jar for 0.5-24 hours and then taking it out.

7. The surfactant according to claim 1 is polyethylene glycol (molecular weight can be from 200-12000) or sodium dodecylbenzene sulfonate or sodium lauryl sulfate.

8. The surfactant according to claim 1 is polyvinyl pyrrolidone.

9. The coupling agent according to claim 1 is a silane coupling agent (KH550, KH560, KH570) or a titanate coupling agent.

10. The coupling agent according to claim 7 is a silane coupling agent (KH550, KH560, KH570) or a titanate coupling agent.

11. The surfactant according to claim 10 is polyvinyl pyrrolidone or polyethylene glycol or sodium dodecylbenzene sulfonate.

12. The coupling agent according to claim 10 is a silane coupling agent (KH550, KH560, KH570) or a titanate coupling agent.

13. The film-forming substance according to claim 2 is water-based polyurethane or alcohol-soluble resin.